Health Risk Assessment of Heavy Metals in Samples of some Edible Vegetable Leaves sold in Samaru Market - Funtua, Mustapha Ado; Jimoh, Abdullateef; Yilleng, Moses Titus (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The present study was conducted to determine the concentration of heavy metals in some selected vegetables bought in Samaru market, Sabon Gari Local Government Area, Kaduna State Nigeria. Essential and non-essential heavy metals such as Cd, Cr, Fe, Zn, Pb, and Ni were investigated in Ugu leaf (Fluted pumpkin), Amaranthus caudatus, and Hibiscus cannabitus leaves by using Atomic Absorption Spectrometry (AAS). Plants leaves showed different metal mean concentrations concentration in the range of: Cd, Cr, Fe, Zn, Pb and Ni in Fluted pumpkin (Telfairia occidentalis) were: 0.060, 18.170, 275.670, 12.830, 0.040, and 0.050; in Amaranthus caudatus were, 0.080, 5.000, 128.000, 8.670, 0.040 and 0.900 mg/kg; in Hibiscus cannabitus were 1.100, 8.670, 278.670, 1.530, 0.530 and 0.050 mg/kg and in the soil were 0.060, 18.170, 275.670, 1.530, 0.040 and 0.900 mg/kg respectively. Other heavy metals were present in low quantity. The purpose of this study was to identify each type of metal associated with a given vegetable contaminated by environmental pollution and also to highlight the toxic heavy metals present in these vegetables. Health risk index (HRI) of these heavy metals have been determined on three common edible vegetable samples, only Fe in all the plants analysed exceeded the maximum permissible limit and it has to be monitored in order to prevent high Fe concentration related diseases/ailments. Most of the heavy metals concentrations values obtained were below the permissible limit recommended by WHO/FAO.